2020
DOI: 10.1038/s41598-020-77268-8
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic fluorescence-lifetime imaging of NADH and protoporphyrin IX improves the detection and grading of 5-aminolevulinic acid-stained brain tumors

Abstract: Maximal safe tumor resection remains the key prognostic factor for improved prognosis in brain tumor patients. Despite 5-aminolevulinic acid-based fluorescence guidance the neurosurgeon is, however, not able to visualize most low-grade gliomas (LGG) and infiltration zone of high-grade gliomas (HGG). To overcome the need for a more sensitive visualization, we investigated the potential of macroscopic, wide-field fluorescence lifetime imaging of nicotinamide adenine dinucleotide (NADH) and protoporphyrin IX (PPI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 54 publications
1
33
0
Order By: Relevance
“…We correlated FD-FLIM measurements with the respective PpIX signal contribution as a ground truth. Autofluorescence lifetimes were found to be in the range of about 0.8 to 2 ns (32,33), which was substantiated by a non-pathological sample within this study. The multimodal approach revealed how even weak PpIX concentrations in tissue led to an increase of the measured lifetime respective to tissue autofluorescence.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We correlated FD-FLIM measurements with the respective PpIX signal contribution as a ground truth. Autofluorescence lifetimes were found to be in the range of about 0.8 to 2 ns (32,33), which was substantiated by a non-pathological sample within this study. The multimodal approach revealed how even weak PpIX concentrations in tissue led to an increase of the measured lifetime respective to tissue autofluorescence.…”
Section: Discussionsupporting
confidence: 83%
“…Based on our previous results (32,35), we hypothesize that weak PpIX concentrations as found in LGG and weakly infiltrated tumor tissue of HGG increase the fluorescence lifetime respective to non-pathological brain parenchyma when measured with frequency-domain (FD)-FLIM. To investigate the extent to which PpIX fluorescence can be distinguished from a dominating autofluorescence background, we developed a multimodal surgical microscope.…”
Section: Introductionmentioning
confidence: 87%
“…These data indicate that the tumor affects the biochemical state of surrounding tissue. For the rat models, it is no surprise that healthy brain tissues in the tumor-bearing animals are affected because the size of the tumor is large, so both the infiltration of the tumor cells in the brain and the mechanical pressure of the tumor on the surrounding tissues are inevitable ( 4 , 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…sodium fluorescein or indocyanine green) has proven to be a useful technique to improve the resection, but the challenges associated with non-specific distribution of the fluorophore, timing and the subjective assessment of fluorescence still remain ( 3 ). In addition, the use of 5-ALA in most cases does not allow to detect low grade gliomas, although it seems to be possible based on the fluorescence lifetime information ( 4 ). To avoid non-specific distribution of the fluorophores, fluorescent reporters targeting epidermal growth factor (EGF) receptor or other tumor specific molecules have been reported ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Autofluorescence FLIM of ex vivo tissues have also been investigated this year. Erkkila et al showed that FLIM of NAD(P)H, and protoporphyrin identify tumor margins in low-and highgrade human gliomas 31 [Fig. 3(a), right panel].…”
Section: Autofluorescence Flim Applicationsmentioning
confidence: 99%